Naturalization and citizenship: who benefits? : liberalizing access to citizenship has labor market benefits for immigrants and can improve their assimilation - Gathmann, Christina (IZA world of labor, 2015)
Politicians, the media, and the public express concern that many immigrants fail to integrate economically. Research shows that the option to naturalize has considerable economic benefits for eligible immigrants, even in countries with a tradition of restrictive policies. First-generation immigrants who are naturalized have higher earnings and more stable jobs. The gains from citizenship are particularly apparent among immigrants from poorer countries. A key policy question is whether naturalization causes labor market success or is taken up by those immigrants who would anyway be most likely to succeed in the labor market.
Keywords: Aufsatz in Zeitschrift